Molecular detection of Anaplasma marginale in Arabian Camels (Camelus dromedarius) in Riyadh, Saudi Arabia - Emad Omer; Mohammed Elfehid; Abdelatiff Alwazan; Abdulaziz S. Alouffi; Fahdah A. Alshammari; Ibrahim Eldesoukey; Khaled Sultan (Journal of the Saudi Society of Agricultural Sciences)
Anaplasmosis, an underestimated tick-borne disease, is a common infection in ruminants including Arabian camels. To our knowledge, few studies have been carried out in Saudi Arabia to identify via molecular methods Anaplasma spp. that infect camels. Therefore, this study was performed to detect and identify Anaplasma spp. in Arabian camels in the Riyadh area of Saudi Arabia.A total of 644 whole blood samples were collected between January 2018 and December 2019. Giemsa-stained, thin blood smears were examined microscopically and then a polymerase chain reaction (PCR) for selected positive samples had been carried out that targeted the specific region of major surface protein 5 (MSP5) of Anaplasma marginale.A total of 273 out of 644 (42.39%) camels were found to be positive by microscopic examination for Anaplasma spp. Amplification of MSP5 gene specific for A. marginale was done.Results of the current study successfully detect A. marginale in camels in Saudi Arabia. To the best of our knowledge, this is the first molecular study that has confirmed the presence of A. marginale in Saudi camels. The MSP5 gene provides a new attractive diagnostic target for detection of A. marginale. Also, the current study highlights the significant levels of camel anaplasmosis in Saudi Arabia.